2018
DOI: 10.22214/ijraset.2018.1266
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Analysis of Aluminium 6063, Graphite and CNT (Hybrid) Nano Composites by using Powder Metallurgy

Abstract: The aluminum-graphite and carbon nano tubes hybrid composites have been successfully fabricated by powder metallurgy and hot extrusion techniques. The hybrid nano Composite displayed uniform dispersion of gr-cnt and an excellent interfacial bonding with the aluminum matrix micro structural characterization revealed that composite displayed uniform dispersion of gr-cnt and excellent interfacial bonging with aluminum bonding. Hardness testing showed that there occurs a significant increment in hardness value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Ishtiaq Ahmed et al [8] studied on analysis of Aluminium 6063, CNT and Graphite (Hybrid) Nano Composites by using powder metallurgy. The results revealed that there is significant increase in hardness value of the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%
“…Ishtiaq Ahmed et al [8] studied on analysis of Aluminium 6063, CNT and Graphite (Hybrid) Nano Composites by using powder metallurgy. The results revealed that there is significant increase in hardness value of the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%